Anomalously fertile subcontinental lithospheric mantle beneath the intracontinental Canning Basin, Western Australia - Moro, P S; Aitken, A R A; Kohanpour, F; Jessell, M W (Geophysical journal international, 2024)
SUMMARY Many intracontinental basins form as broad depressions through prolonged, slow subsidence of the continental lithosphere. Such long-lived basins can record lithospheric processes over hundreds of millions of years, serving as important archives of lithospheric evolution. Since continental amalgamation in the Mesoproterozoic, the lithosphere beneath the intracontinental Canning Basin has been subject to several tectonic events, with extensive crustal reworking evidenced through different upper crust data sets. However, knowledge of the structure of the subcontinental lithospheric mantle is lacking. As a consequence, understanding the coupled evolution between surface and deep lithospheric processes, crucial to resolving basin formation, development and survival, remains problematic. Here, we combine geochemical, geophysical and petrophysical data within a thermodynamic modelling framework to determine the thermochemical properties, rheology, density and seismic structure of the lithospheric and sublithospheric mantle beneath the Canning Basin. The results indicate a thick, rigid lithosphere with a maximum thickness of 185 km and strength of ca. 1 × 1013 Pa m, and an anomalously Fe-enriched subcontinental lithospheric mantle with a Mg# of 88.6. This mantle structure is not consistent with pre-collisional fragments or a Precambrian collisional setting and may reflect magmatic refertilization during high-volume mafic magmatic events. Potential candidate events are the ∼1070 Ma Warakurna, ∼825 Ma Gairdner and ∼510 Ma Kalkarindji Large Igneous Provinces. The youngest of these is temporally and spatially correlated with and therefore interpreted to have influenced the Canning Basin formation. We propose that refertilization caused a negatively buoyant subcontinental lithospheric mantle and prolonged subsidence and preservation of the basin, while the strong lithosphere ensured lithospheric stability and longevity.